2013
DOI: 10.1093/cid/cit272
|View full text |Cite
|
Sign up to set email alerts
|

Human Infections With Influenza A(H3N2) Variant Virus in the United States, 2011-2012

Abstract: BACKGROUND. During August 2011-April 2012, 13 human infections with influenza A(H3N2) variant (H3N2v) virus were identified in the United States; 8 occurred in the prior 2 years. This virus differs from previous variant influenza viruses in that it contains the matrix (M) gene from the Influenza A(H1N1)pdm09 pandemic influenza virus. METHODS. A case was defined as a person with laboratory-confirmed H3N2v virus infection. Cases and contacts were interviewed to determine exposure to swine and other animals and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 24 publications
1
85
0
Order By: Relevance
“…This HA gene was likely introduced from humans into swine in 2010 or 2011, and has since circulated and evolved in swine to be genetically and antigenically different from both previous and currently circulating human seasonal influenza A(H3N2) viruses (3). The viruses in the remaining two specimens had HA genes similar to those of swine-origin H3N2 influenza viruses circulating in the U.S. swine population since 1998, and previously identified in human H3N2v virus infections in the United States since 2009 (4,5). Preliminary analysis suggests that the viruses identified in all human specimens were nearly identical to H3N2 viruses detected in swine at agricultural fairs in Michigan and Ohio.…”
Section: Laboratory Investigationmentioning
confidence: 52%
“…This HA gene was likely introduced from humans into swine in 2010 or 2011, and has since circulated and evolved in swine to be genetically and antigenically different from both previous and currently circulating human seasonal influenza A(H3N2) viruses (3). The viruses in the remaining two specimens had HA genes similar to those of swine-origin H3N2 influenza viruses circulating in the U.S. swine population since 1998, and previously identified in human H3N2v virus infections in the United States since 2009 (4,5). Preliminary analysis suggests that the viruses identified in all human specimens were nearly identical to H3N2 viruses detected in swine at agricultural fairs in Michigan and Ohio.…”
Section: Laboratory Investigationmentioning
confidence: 52%
“…In the United States, one of the new genotypes that resulted from reassortment with pH1N1 viruses is H3N2v, with a high profile in 2011 and 2012, which was a triple-reassortant H3N2 virus that acquired the MP-pdm segment. This particular H3N2v genotype is notable because it has been associated with Ͼ330 human infections since 2011, mostly in children attending agricultural fairs (30). Although the largest number of cases occurred during the summer of 2012, with fewer cases observed during 2013 and 2014, the equivalent H3N2 virus continues to circulate in U.S. swine populations, and the risk of another major outbreak in the future remains.…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, previous studies have shown that A(H3N2)v virus transmitted efficiently to naive ferrets by respiratory droplets (12). However, there has been no evidence of sustained human-to-human transmission of A(H3N2)v virus and most of the rare, limited human-to-human transmission has occurred between children within familial clusters or within day-care settings (13,14). It is conceivable that the lack of efficient A(H3N2)v virus transmission in humans is partly due to the presence of preexisting cross-reactive immunity to this virus in the human population.…”
mentioning
confidence: 99%